Reconstruction of Legal Arrangements of Fiduciary Guarantees Reviewing Effectiveness In Leasing Practices - Suris, Nabila; Maimuna; Fina Ainun Jazilah; Husni Mubarok; Ahmad Musadad (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
This article examines the reconstruction of the regulation of fiduciary security rights in order to improve the effectiveness of implementation and legal protection of collateral objects, especially in leasing practices in Indonesia. This research is motivated by various problems in the field, such as non-compliance of leasing companies in registering fiduciary guarantees, unilateral execution without a fiduciary certificate, and unlawful forced withdrawal of vehicles when the debtor defaults. In fact, registration of fiduciary guarantees is very important because it provides executorial power and gives birth to property rights attached to the principles of droit de suite, droit de preference, specialty, and publicity. Through a normative juridical approach by analyzing the applicable regulations and case studies in the field, this research finds that the weak compliance of business actors and the lack of government supervision are the main factors for the low effectiveness of the implementation of fiduciary guarantees in leasing. Therefore, it is necessary to reconstruct legal arrangements that emphasize the obligation to register fiduciary guarantees and strengthen fair execution mechanisms, in order to create balanced legal protection between creditors and debtors. In addition, education for the public and strengthening supervision from relevant authorities are important steps so that the implementation of fiduciary in leasing runs according to the principles of justice and legal certainty.